Remarkable Geosites of Quito That Are Aspiring to Be a UNESCO Global Geopark - Theofilos Toulkeridis; Grace Tatiana Páez-Barrera; María Fernanda Chávez-Melo; Gabriela Fernanda Alvarez-Calupiña; Pablo Marcelo Espinoza-Carriel; Danny Fernando Chiriboga-Barba; Florencio Delgado-Espinoza; Melany Velasquez-Muela; Wilson Salas-Álvarez; Catherine Frey; Izar Sinde-González (Geosciences)
An analysis of different geosites as territories of high geo-biodiverse value located within the Metropolitan District of Quito (DMQ) in Ecuador is performed based on the geoscientific inventory of thirty-six territorial zones and their geological history, cultural, and biological wealth. This is based on years of research and was complemented with the Geosites Assessment Model (GAM) methodology, the application of the criteria of which results in an impartial quantitative evaluation of each of these geosites, resulting in the determination of geographic areas with high tourist, archeological, and social potential. It also establishes a baseline to generate conservation strategies, scientific dissemination, and the determination of priorities in the management of the conservation of the geological heritage of the DMQ in Ecuador. The geological and geomorphological evolution of the DMQ grants this region a variety of sites formed by mainly cretaceous and quaternary volcanic and sedimentary deposits, geological faults, and other remarkable formations or sequences, which, together with the geoarchaeological sites, give a unique geohistorical value to the DMQ. In this context, the protection of each of the regionally important study sites for their scientific, educational, and cultural value in the geological area, as well as their scenic beauty and biodiversity, is essential. All of these attributes will be input to the future sustainable development approaches of the proposed UNESCO-DMQ Global Geopark by academic experts and researchers working in this territory. Additionally, this study also defines the need for the protection of each study area. The results of the evaluation will help to plan the effective management of the geosites based on their strengths and weaknesses and thus promote the Global Geopark. In this context, the value of the geodiversity of the DMQ has been recognized in this research, specifically for each of the geosites proposed as part of the UNESCO Global Geopark; the DMQ project, highlighting this geological and biodiverse heritage, contributes to direct benefits for the community and at an international level.